Optimization of Radiation and Electric Current Storage in a Dye-Sensitized Solar-Cell System Based FTO/TiO2 /Acy/PVDF/C/FTO Modules for Electrical Equipment Applications - Kurniawan, Muhammad Ridho Hafid; Cahyani, Sinta Anjas; Kusumawati, Nita; Setiarso, Pirim; Muslim, Supari (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Indonesia has an electrification rate exceeding 99% as of 2020, yet it faces increasing electricity demands amid declining fossil fuel availability. Solar energy, particularly through DSSC, presents a promising renewable alternative, benefiting from an abundant radiation potential of up to 120.000 TW. DSSC have garnered significant attention due to their thin design, high efficiency, ease of fabrication, and environmental friendliness. The DSSC module was designed using two FTO glass plates as electrodes, with an anode surface area of 3 cm2. The TiO2 photoanode was prepared using a casting knife technique and then sintered at 450°C for one hour. This was followed by sensitization with anthocyanin dye derived from the butterfly pea flower under acidic conditions for 24 hours to ensure the stability of the compound. The electrolyte system consisted of PVDF NF membranes soaked in the electrolyte solution for one hour to prevent leakage, thus completing the FTO/TiO2/PVDF/C/FTO system. Performance optimization involved arranging 20 DSSC cells in a mixed series-parallel circuit configuration. Electrical parameters were measured using a multimeter under various lamp irradiation durations. The optimal efficiency was achieved with 5 hours of irradiation, resulting in 2.050 mV and 23.5 x 10-3 µA. When integrated into a battery system, the DSSC module demonstrated effective current storage stability over 6 hours, indicating strong potential for practical implementation in sustainable energy generation for real-world applications.